ACCENT VARIATION AND LISTENING LEARNING STRATEGIES: STUDENTS’ EXPERIENCES IN UNDERSTANDING ACCENTED ENGLISH - Siffa Annisa Fitri Ramadhani; Yuanita Susanti; Tita Kinasih Intani; Vicky Hidantikarnillah (Tadulako University, 2026)
English as a global lingua franca exposes EFL learners to various English accents that often create difficulties in listening comprehension. However, limited studies have explored how learners use strategies to cope with accent variation. This study investigated students’ learning strategies and experiences in understanding accented English in an Advanced Listening class. Using a mixed-methods sequential explanatory design, the study involved 30 university students in Tangerang. Data were collected through listening tasks, questionnaires, and semi-structured interviews. The findings showed that students frequently used cognitive and metacognitive strategies, such as focusing on key words, predicting meaning, monitoring comprehension, and using subtitles to support understanding. Memory, affective, and social strategies were also applied, although less intensively. Students experienced difficulties related to speech rate, pronunciation differences, and unfamiliar accents, especially non-native varieties. Despite these challenges, students demonstrated positive attitudes and strong self-efficacy toward improving their listening ability through practice and exposure. The study concludes that listening to accented English is a multidimensional process requiring strategic competence, emotional regulation, and broader exposure to diverse English varieties. These findings imply the need for strategy-based listening instruction and increased integration of accent diversity in EFL classrooms.